S33 Performance of EBUS-TBNA in the pathological subtyping and molecular testing of non-small cell lung cancer (NSCLC) in a UK thoracic oncology centre. (12th November 2015) - Al-Najjar, H; Evison, M; Martin, J; Barber, P; Crosbie, P; Booton, R
Abstract : Introduction: The categorisation of NSCLC into squamous and non-squamous subtypes is an important requirement for the optimisation of patient care as this may modify chemotherapy regimens and direct molecular testing. The lung cancer national audit highlights the need to minimise the rate of NSCLC not otherwise specified (NSCLC-NOS). 1 The aim of our study was to determine whether samples obtained by endobronchial ultrasound guided-transbronchial needle aspiration (EBUS-TBNA) could be used to pathologically subtype NSCLC and provide sufficient material for molecular testing. Methods: A prospectively maintained database of consecutive patients with suspected lung cancer referred to our unit, a UK regional thoracic oncology centre, was analysed. All patients diagnosed with NSCLC by EBUS-TBNA cytology at our centre between Sept 2013 and Sept 2014 were included in the study. Results: A total of 89 patients were diagnosed with NSCLC using EBUS-TBNA. The pathological subtypes were: n = 46 (51.7%) squamous cell carcinoma, n = 41 (46%) adenocarcinoma and n = 2 (2.2%) NSCLC-NOS. All samples with a new diagnosis of non-squamous subtype were sent for EGFR mutation analysis, with sufficient material in 97% (n = 35/36) and one activating mutation was identified. ALK analysis was successfully performed in all 5 samples in which this was requested. Additional molecular testing was requested in 9 samples with sufficient material in 89% (n = 8/9). Conclusions: EBUS-TBNA cytology can be used to successfully subtype NSCLC and provide adequate material for molecular testing in the majority of cases. The rate of NSCLC-NOS in our study (2.2%) compares favourably with local cancer network (13.5%) and national (12.9%) figures. Reference: 1 National lung cancer audit report 2014 doi http://www.hscic.gov.uk/catalogue/PUB16019/clin-audi-supp-prog-lung-nlca-2014-rep.pdf